A rare case: Pentrating craneoencefalic trauma by knife. Updating the diagnosis and treatment. - García Ordóñez, Galo Fabián; Guillermo Cornejo, Andrea Priscila; García Ordóñez, Luis Fernando; García Ordóñez, Danny Renán; Aguilar Castillo, Jenner Quilson; Villacis Sandoval, Jorge Rodrigo (Revista Argentina de Neurocirugía, 2021)
Craneoencephalic penetrating trauma represents about 0.4% of cases, few are described in the literature, therefore, there is no protocolized management of them.We describe a case of a 24-year-old male patient who suffers penetrating trauma at left parietal region with a "knife", leaving the blade embedded. Simple Computed Tomography of the Skull with Reconstruction in 3 dimensions plus angiography, confirms the diagnosis without vascular compromise. The complete removal of the foreign body was performed, without complications. Evolution is favorable and was discharged with improvement neurological symptoms.This type of trauma is an emergency that can put the life at risk depending on the affected area. The removal of the foreign body must be performed in a hospital environment due to the involvement of large vessels. There must be a high diagnostic suspicion associated with the antecedent.
Keywords: Post-Head Injury; Gun Violence; Knife; Craniotomy; Cerebral Hemorrhage